Pengaruh Kompetensi, Lingkungan kerja, dan Budaya Organisasi terhadap Kinerja karyawan dan Motivasi Kerja sebagai variabel intervening - Laili Dian Safitri; Andhika Syahputra; Aulia, Reva Cindy; Sevtiani Isty Lazumi; Endira Efiani; Ni Nyoman Sawitri (Draf Solusi Indonesia, 2024)
A B S T R A C T This research on human resource management discusses about The Influence of Competence, Work Environment, and Organizational Culture on Employee Performance and Work Motivation. In this study, qualitative research methods are used. The purpose of this article is to build a hypothesis of influence between variables that will be used in the following research; The object of research is in online libraries, Google Scholar, Mendeley and other academic online media. The research method with Library Research is sourced from e-books and Open access e-journals. The results of this article show that Competence affects employee performance, Work environment affects employee performance, Organizational culture affects employee performance, Work motivation affects employee performance